2011
DOI: 10.1055/s-0039-1698859
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mental Index, Mandibular Cortical Index and Panoramic Mandibular Index on Dental Panoramic Radiographs in the Elderly

Abstract: Objectives:The aims of this study were to evaluate the influence of gender and dental status on the mental index, mandibular cortical index and panoramic mandibular index from dental panoramic radiographs in elderly who had osteoporosis or did not have osteoporosis.Methods:Panoramic radiographs of 487 elderly dental patients (age range 60–88 years) were evaluated. It were recorded osteoporotic status according to the patients’ medical anamnesis and values of the mandibular cortical index (MCI), panoramic mandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 34 publications
5
57
3
3
Order By: Relevance
“…In our study, neither of the groups had any significant correlation between the right PMI value and age, however found a weak but statistically significant correlation between the left PMI value and age in only healthy individuals. The data we obtained was not consistent with the data from Dagistan & Bilge (2010), Ledgerton et al, Gulsahi et al (2008), Hastar et al (2011), andKnezovic´ Zlataric´ et al (2002). This inconsistency might be explained due to difference in studied sample groups and uneven dispersion of individuals in the age groups.…”
Section: Discussioncontrasting
confidence: 95%
“…In our study, neither of the groups had any significant correlation between the right PMI value and age, however found a weak but statistically significant correlation between the left PMI value and age in only healthy individuals. The data we obtained was not consistent with the data from Dagistan & Bilge (2010), Ledgerton et al, Gulsahi et al (2008), Hastar et al (2011), andKnezovic´ Zlataric´ et al (2002). This inconsistency might be explained due to difference in studied sample groups and uneven dispersion of individuals in the age groups.…”
Section: Discussioncontrasting
confidence: 95%
“…Hastar et al17 reported that MCW, the MCI, and the PMI exhibited statistically significant differences between patients with and without osteoporosis. However, Klemetti et al8 suggested that the correlation between bone mineral density and the PMI was weak.…”
Section: Discussionmentioning
confidence: 99%
“…These radiomorphometric parameters have been extensively used in previous studies, especially those related to low bone mineral density. (7) All of the panoramic radiographs examined in the present study were captured using the same radiograph machine, and the same software that was recommended by the manufacturer. In this manner, discrepancies in magnification caused by variations in the settings of different machines were avoided.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Dental panoramic radiography is useful as a routine procedure in implant therapy. (1,(4)(5)(6)(7) In some cases, not only the implant sites but also the gonial angle (GA), inferior lower cortical bone under the mental foramen, floor of the maxillary sinus, mandibular canal, and mandibular condyle are the focus of implant therapy screening. (8)(9)(10)(11)(12)(13) Factors such as age, gender, and dental status of the patient, whether they wear partial or complete dentures, and how long have worn them must determine when morphological changes of the mandible are assessed on a dental panoramic radiograph.…”
mentioning
confidence: 99%